Role of ecological engineering technique to manage insect pest problems in rice field of West Bengal - Dutta, Prasakha; Satpathi, Chitta Ranjan (Indian Journal of Plant Protection, 2025)
Conventional pest management practices have brought serious threat to environmental sustainability thus the present study is focused upon a very new approach of pest management called Ecological Engineering Technique (EET). It is to divert the insect pests from our target crops to some other host source by managing the farmland plantations in such a way so that the natural agro ecosystem gets changed or the natural enemies of the insect pests get attracted to the field in response to volatiles attracting them in favour of our target crop against the insect pests. Recently an attempt was made in Eastern India to judge if rice insect pest problem could be solved through ecological management in some rice growing areas of Southern part of West Bengal in RRS Chakdah, Nadia, West Bengal. Rice was sown in subplots in Randomized Block Design (RBD) bordered by pulse crops like Frenchbean (Phaseolus vulgaris), Cowpea (Vigna ungiculata), Soybean (Glycine max) flowering plants like Cosmos (Cosmos bipinnatus), Marigold (Tagetes erecta), spice crops like Corriander (Coriandrum sativum), Fennel (Foeniculum vulgari), vegetable crop Okra (Abelmoschus esculentus) a fodder crop like Napier grass (Pennisetum benthami) and sole rice crop as control in 10 treatments each having 3 replications. Obsevations showed that there was reduction in Brown plant hopper and rice stem borer population along with notable presence of parasitoid and predatory wasps in rice subplots with other crops in border. Stem borer population was least in treatment made in napier grass (54%) kept as border crop, followed by fennel (42.64%), corriander (38.13%), frenchbean (27.62%), marigold (42.04%), cosmos (21.02%), soybean (19.21%), okra (16.21%), cowpea (12.01%). The population of brown plant hopper (BPH) was mostly reduced in rice crop in case of marigold (30%), fennel (30%), frenchbean (30%) as border crop followed by corriander (25%), cowpea (15%), soyabean (10%), okra (5%) as compared to control. Maximum number of parasitoid wasps were found in case of coriander (11) followed by fennel (9), marigold (8). Thus napier grass, fennel, corriander, frenchbean, cowpea, soyabean and cosmos can be grown on bunds around rice field to reduce Stem borer population and marigold, fennel, frenchbean, corriander can be grown around rice field to reduce Brown plant hopper population. This bund cropping techniques leads to modification of existing ecology interfering with the insect chemical communication. This practice should also be acceptable to the farmers as it can reduce the problem of multiple sprays of chemical insecticides to manage insect pests and thus reduce the cost of cultivation. Besides as the average length of bund is 300 meters /acre hence farmers can plant 300 cowpea, or 900 marigold plants over bund which can fetch about Rs 1 to 1.5 lakh spending only Rs 10, 000/acre. Field bund tree litters grasses and herbs can be used for maintenance of overwintering sites of lady bird beetles.